ENGLISH LITERACY ERRORS OF CHILDREN WITH VISUAL IMPAIRMENTS - Rochyadi, Endang; Hanafi, Moh; Fatimatuzzahra, Ana (EDUTECH, 2020)
English literacy is inseparable from the four interrelated aspects of skills which are listening, speaking, reading, and writing aspects. Among the four English literacy skills, writing is considered the most difficult skill, so we need a special technique to practice these skills. For children with visual impairments, writing English vocabulary becomes a challenge especially during the learning process, limitations in seeing make the children often experience writing errors especially in writing structure because children only write English vocabulary based on what is heard, especially from those speakers who are not native speakers. The purpose of this study is to explain the analysis of English literacy errors of children with visual impairments aiming to improve English vocabulary writing literacy skills. The study uses qualitative methods with descriptive methods. Data collection techniques were carried out using observation, interview, and documentation (data triangulation) techniques. The results showed that writing literacy errors that often arise are replacing, omitting and adding letters to English vocabulary based on the results of sound listening skills and the ability to remember vocabulary that the children already knew.Literasi bahasa Inggris tidak terlepas dari empat aspek keterampilan yang saling terkait yaitu aspek mendengarkan, berbicara, membaca dan menulis. Di antara keempat keterampilan literasi bahasa Inggris, menulis dianggap sebagai keterampilan yang paling sulit, sehingga diperlukan teknik khusus untuk melatih keterampilan tersebut. Bagi anak tunanetra, menulis kosa kata bahasa Inggris menjadi tantangan terutama selama proses pembelajaran, keterbatasan dalam melihat membuat anak sering mengalami kesalahan penulisan terutama dalam struktur penulisan karena anak hanya menulis kosakata bahasa Inggris berdasarkan apa yang didengar, terutama dari penutur yang bukan penutur asli. Tujuan dari penelitian ini adalah untuk menjelaskan analisis kesalahan literasi bahasa Inggris anak tunanetra yang bertujuan untuk meningkatkan kemampuan literasi menulis kosakata bahasa Inggris. Penelitian ini menggunakan metode kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan teknik observasi, wawancara dan dokumentasi (triangulasi data). Hasil penelitian menunjukkan bahwa kesalahan literasi menulis yang sering muncul adalah mengganti, menghilangkan dan menambahkan huruf pada kosakata bahasa Inggris berdasarkan hasil keterampilan mendengar suara dan kemampuan mengingat kosakata yang sudah diketahui anak.